Enhancing Diagnostic Accuracy and Patient Safety: The Collective Efforts of Laboratory, Anesthesia, Radiology, Nursing, Health Assistant and Pharmacy Teams - Muhammad Nasser Ahmed Anbari (7), Mousa Hassan Yahya Suwayyid (8), Khalid Qasem Ahmed Zaylay (9), Mohammed Ahmed Essa Zain Aldeen (10), Abdulsalam Abdullah Melfi Alqahtani (11), Mohammed Mastour Abutalib(12)., Mohammed Qasem Ibrahim Masoud (1), Majed Qasem Ibrahim Masoud (2),Yahya Ali Sultan Nahari (3)Qasem Ahmed Ibrahim Mushafa (4), Mohamed Ahmed Ibrahim Majaridi (5), Mohammed Mansour Abuhathaf (6) (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Accurate diagnosis and optimal patient safety are fundamental goals of healthcare. While individual teams play crucial roles, effective collaboration across disciplines is imperative. This paper examines the roles and challenges of key clinical teams Laboratory, Anesthesia, Radiology, Nursing, Health Assistant, and Pharmacy. It identifies strategies to strengthen interdisciplinary collaboration and analyzes their impact on diagnostic accuracy, patient safety, and quality of care. This review examines strategies shown to enhance collaboration between key teams like Laboratory, Radiology, Nursing, Anesthesia, Health Assistants and Pharmacy. It also analyzes peer-reviewed studies evaluating the impact of targeted interprofessional collaboration approaches on team dynamics and identifies qualitative methods to explore underlying contextual factors. A literature search was conducted in PubMed, CINAHL, and Web of Science databases using keywords like "interdisciplinary collaboration", "diagnostic accuracy", "patient safety", "clinical teams". Relevant articles published between 2015-2022 were reviewed for each clinical team's functions, collaboration barriers, and improvement strategies. Credible reports from WHO, Joint Commission and professional bodies supplemented the findings. The Laboratory team plays a vital role in disease diagnosis and treatment monitoring through clinical tests and analyses. However, lack of timely communication between Laboratory and clinical teams can delay diagnoses or treatment plans. The Anesthesia team ensures patient safety and comfort during medical/surgical procedures through monitoring, airway management and administration of anesthesia.The Nursing team is central to continuous monitoring, medication administration and health education of patients. However, nurse understaffing and ineffective shift-to-shift handoffs challenge the delivery of safe, quality care. Health Assistants play a supportive role through basic patient assessments, sample collection and ward duties. In summary,This review highlights the crucial, yet interdependent roles of key clinical teams in healthcare delivery. Strategies like multidisciplinary rounds, shared documentation systems and structured communication protocols can strengthen teamwork dynamics and information flow. Ultimately, interdisciplinary collaboration is fundamental to enhancing quality and safety in healthcare.To conclude, diagnostic challenges today span multiple specialties and demand a unified, well-orchestrated response from Laboratory, Radiology, Anesthesia, Nursing and other groups. The paper's overarching message is clear - by coming together through targeted collaboration strategies, our collective efforts hold immense promise to advance diagnostic accuracy, patient safety and healthcare quality overall. Moving forward in a spirit of partnership will undoubtedly serve our patients and professions